(untitled) (Kathmandu University Medical Journal, 2022)
When a child is born before 37 weeks or 259 days of pregnancy, it is termed as preterm birth. Pre-term birth is prevalent in both developed and developing country. However, difference lies in their survival. In lower and middle income countries, most preterm babies die due to lack of even simple interventions. India ranks top in the world for deaths due to complications of preterm birth. Similarly, other South Asian countries, Pakistan, Bangladesh, Afghanistan and Nepal rank 3rd, 6th, 9th and 20th in the same. The aim of this review paper is to provide a landscape analysis on the burden of pre-term birth and challenges in the context of South Asian region. Databases such as PubMed, Scopus and Google Scholar were searched from 2000 to 2020 and 27 articles are included in the study. It was found that pre-term birth causes huge burden in the form of morbidity, mortality as well as socio economic losses. Preterm birth was associated with increased sepsis, cardiovascular disease, respiratory illness, hypothermia, neurological and gastrointestinal complications. South Asian countries have distinct challenges in eliminating or reducing preterm births which are: poor quality health surveillance data, inadequate trained health workforce, insufficient finance and funding, service delivery and other methodological challenges. Ending pre-term birth is important as it is directly related to Sustainable Development Goal 3. Therefore, there should be increase in priority given to increase financing, quality data gathering, adopting innovative measures as well as joint efforts of all the sectors to control the pre-term birth.